(3JMaI GdENhGf aj GdoNda Hjf GdTGWHjI hGdYfhGfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,(B833 (3g`s ((3eMeO Hf CMeO Hf eMeO GdENejei s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B,(3HYO agPg JMaI GdENhGf ai GdNda Hjf GdTGWHjI hGdYfhGf EP cGf GdYfhGf JCdja GdEeGe CHj WGgQ ESeGYjd Hf Nda GdebQi s
(3BNQgG (B:s
(3hde jJYQV Edi GdJcHjQ ai BNQ GdfGS , hdcf jage ef bhdg GdJcHjQ ai EKQ cd ShQI MJi JNJe , ajcHQ Hjf GdfGS hGdaGJMI bWYkG JeJ JMaI GdENhGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JLhjO hbQGAGJ (B21) s
Keywords: (3GdbQGAGJ hGdJLhjOs